Literature, Violence and Crisis. Opinions over the Political and Proleptic Gesture in Literature [Literatura, Violencia y Crisis. Pareceres Sobre el Gesto Politico y Proleptico en la literatura1 - Navarrete-Barria, S (Pontificia Universidad Catolica de Chile 1, 2020)
In this essay I propose an aesthetic and political reading of the recent Chilean fiction narrative, aiming at tracing the different ways in which this narrative reaches the reader and what it does in such encounters. My general postulate proposes that in this narrative it is possible to trace a work of appealing to the reader so as to enable for the violence to emerge as a critical tool to interpret our reality. I analyze works from post-dictatorship to the present day to delimit certain discursive lines that fracture the normality imposed by the transitional regimes, and bring readers closer to the abyss of the crisis and to the different paths where violence runs through in our daily lives. How much of the crisis we are experiencing was already recorded in the recent narrative How did this inscription evolve What nuances can we distinguish © 2020 Instituto de Estetica - Pontificia Universidad Catolica de Chile.